Study on the effect of compound cultivation on the growth feature and active ingredients content of Salvia miltiorrhiza - Zhang, Luyi; Tao, Shan; Zhang, Yifan; Yang, Yanmei; Peng, Fang; Liao, Hailang; Mao, Changqing; Wan, Xiufu; Wu, Yu; Xu, Zhengjun; Zhang, Chao (Frontiers in Plant Science, 2024)
We investigated the effects of complex cultivation of Salvia miltiorrhiza on microbial communities, secretions, yield and active ingredients, and the mechanism of action between microbial communities, secretions and S. miltiorrhiza growth and development. Neither maize nor soybean was suitable to grow with S. miltiorrhiza, but sesame significantly increased salvinone content, the active ingredient of S. miltiorrhiza, and Tanshinone IIA, Tanshinone I and Cryptotanshinone increased by 27.06, 22.76 and 26.41%, respectively, which increased the abundance and number of microbial communities in S. miltiorrhiza roots. 16S rRNA results showed that the most abundant bacterial phyla were Proteobacteria and Acidobacteriota, and their number increased with compound planting of sesame and S. miltiorrhiza. Salvia inter-root secretions affected the microbial community and Salvia growth and development, and lipids and lipid-like molecules significantly reduced Salvia yield and active ingredients. Overall, different plant secretions can lead to differences in the natural environment and Salvia root growth and development, and the composite planting of sesame with Salvia can